(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The proposed system, an energy efficient and smart power management system.The internet of the things (IOT) is used in the system to monitor the supply received at the loads. This system ensures that maximum power demand is met using the solar energy and if the solar energy is not sufficient, the power demand is satisfied using the AC power grid. The system generates maximum power from solar energy from the PV panels using algorithms even when the solar radiance is low. There is a power saver (battery)that stores the excess power when the power rating of the load is already met.The system is equipped with dual axis sun tracking mechanism for increased power generation from the solar panel. There is also an IOT based controller, being used to monitor the system parameters.